Pengaruh Implementasi SIPD Terhadap Kinerja Pengelola Keuangan Pada Sekretariat Dewan Perwakilan Rakyat Daerah Kota Cimahi - Malasari Dewi; Nia Sumiati; Warman Suryaman (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This study aims to examine the effect of the Implementation of SIPD in Financial Managers at the Secretariat of the Regional People's Representative Council of Cimahi City. The type of research used in this research is explanatory research. The sample of this study were 36 employees managing the finances of the Secretariat of the Regional People's Legislative Assembly of the City of Cimahi. Data processing using SPSS 23.0 software. The test equipment used in this study is descriptive statistics and multiple linear regression analysis. The results of the study show that the implementation of SIPD either simultaneously or partially has an effect on financial performance.